Dlaczego „rozwód notarialny” to złe rozwiązanie? - Kopacki, Marcin (PRAWO i WIĘŹ, 2025)
The paper criticises the idea of introducing notarial divorces. The analysis covers constitutional aspects, the position of notaries in the political system, and axiological values. As an entrepreneur rather than an organ of justice, a notary lacks the key characteristics necessary to ensure a fair hearing of a case. At the same time, when looking at the proposed changes from the perspective of access to informal divorce, far more perfect solutions can be found, such as divorce by advocates and attorney-at-law.